Parental responsibility, young children and healthcare law / Jo Bridgeman. - Bridgeman, Jo (Cambridge University Press, 2007)
This book provides a comprehensive examination of the legal regulation of the provision of healthcare to young children in England and Wales. A critical analysis is given on the law governing the provision of healthcare to young and dependent children identifying an understanding of the child as vulnerable and in need of protection, including from his or her own parents. The argument is made for a conceptual framework of relational responsibilities which would ensure that consideration is given to the needs of the child as an individual, to the experiences of parents gained as they care for their child and that the wider context, such as attitudes towards disability, public health issues or the support and resources available, is examined. This book makes an important contribution to understanding the law regulating the provision of healthcare to young and dependent children and to the development of a discourse of responsibility.